Intervention and mediation effects of target processes in a randomized controlled trial of Acceptance and Commitment Therapy for anxious cancer survivors in community oncology clinics. (June 2022) - Fishbein, Joel N.; Judd, Charles M.; Genung, Sarah; Stanton, Annette L.; Arch, Joanna J.
Abstract: Objective: Acceptance and Commitment Therapy (ACT) is a promising psycho-oncological intervention, but its mechanisms in real-world settings are not fully understood. This study examined core theorized ACT and broader ACT-consistent target processes as mediators of ACT versus minimally-enhanced usual care within a randomized trial for anxious cancer survivors in a community oncology setting. Method: Two core theorized ACT target processes (experiential avoidance and values-aligned behavior, each measured with two instruments) and two broader ACT-consistent target processes (emotional approach coping and self-compassion) were analyzed at pre- and post-intervention as mediators of general anxiety symptoms, cancer-related trauma symptoms, and fear of cancer recurrence ( N  = 134). Results: ACT led to greater increases on emotional approach coping ( p s ≤ .001) and one measure of values-aligned behavior ( p s ≤ .031), and marginal or greater improvement on self-compassion (p s ≤ .055), but not other core ACT target processes. Self-compassion and emotional approach coping mediated ACT's effects on cancer-related trauma symptoms ( p s ≤ .037). Additionally, self-compassion, emotional approach coping, and values-aligned behavior marginally mediated fear of recurrence and general anxiety symptoms improvement ( p s ≤ .088). Conclusion: ACT reduced cancer survivors' anxiety-related symptoms, and especially cancer-related trauma symptoms, most consistently by promoting self-compassion and emotional approach coping.